Prediksi Financial Distress dan Kebangkrutan (Studi Kasus pada Perusahaan Maskapai Penerbangan) - Ira Andriani; Muhamad Umar Mai; Ruhadi Ruhadi (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
The existence of Indonesia's economic growth and the growth of the aviation sector which experienced a contraction in 2020, had an impact on the worsening of financial conditions in the aviation sector. This study aims to determine the prediction of financial distress and the potential for bankruptcy in airline companies. The data collection method used is the documentation method with data analysis techniques using the Altman Z-Score, Springate S-Score, and Mann Whitney Test methods. The results show that PT Garuda Indonesia and Indonesia Air are predicted to experience financial difficulties and the possibility of bankruptcy, while PT Cardig Airlines is not predicted to experience financial difficulties and is unlikely to go bankrupt. Based on the average score, the potential for bankruptcy shows mostly the same results. The difference is only shown in Indonesia Air in 2014 and PT Cardig Airlines in 2019. Based on statistical tests, a significance value of 0.505 was obtained which was more than 0.05 which was rejected and there was no significant difference between the results of the Altman Z-Score and Springate S-Score calculations in predict bankruptcy of airlines. Keywords: Financial Distress, Bankruptcy Prediction, Mann Whitney Test